2008
DOI: 10.1111/j.1469-7610.2008.01901.x
|View full text |Cite|
|
Sign up to set email alerts
|

Does self‐directed and web‐based support for parents enhance the effects of viewing a reality television series based on the Triple P – Positive Parenting Programme?

Abstract: The value of combining self-help approaches, technology and media as part of a comprehensive public health approach to providing parenting support is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 35 publications
7
90
0
1
Order By: Relevance
“…Only three studies examined child abuse outcomes specifically and found a reduction in the incidence of abusive head injuries [49], child maltreatment injuries [56] and child maltreatment cases [52,56]; though one was not statistically significant [52]. However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…Only three studies examined child abuse outcomes specifically and found a reduction in the incidence of abusive head injuries [49], child maltreatment injuries [56] and child maltreatment cases [52,56]; though one was not statistically significant [52]. However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…Eksempler på slike faktorer er styrking av foreldres barneoppdragelse og foreldrefunksjoner, styrket sosial støtte for familier, samt styrking av foreldres og barns mestringsstrategier. Internasjonalt finnes det mange eksempler på intervensjoner, og dokumentasjonen på hvilke av disse som har gode effekter for BAP er økende (Sanders, Calam & Durand, 2008;Murray, Sinclair, Cooper, Ducournau & Turner, 1999;Maybery & Reupert, 2006). Det er imidlertid mange årsaker til at implementering av nye rutiner og tiltak for barn som er pårørende, er krevende.…”
unclassified
“…Parenting outcomes targeted by the interventions included aspects of behaviour, attitudes, and parenting knowledge, with an aggregated overall large effect size (small-to-medium after accounting for uncontrolled studies). As might be expected, effect sizes were smaller overall in the three trials adopting a broader, public health type approach (Bert, Farris, & Borkowski, 2008;Na & Chia, 2008;Sanders, Calam, Durand, Liversidge, & Carmont, 2008), than for those targeted towards specific parent groups or conditions. Four of the interventions were self-directed and unguided, one included parent-initiated email consultations, while three programs provided regular, intensive consultations with a therapist through telephone or videoconferencing software.…”
Section: Beyond Triple P Online: Other Web-based Parenting Programsmentioning
confidence: 76%